30.6k views
5 votes
If h(x)= x-7 and g(x)=x^2, which expression is equivalent to (g•h)(5)

User Tucuxi
by
5.2k points

1 Answer

2 votes

Answer:


\large\boxed{(g\cdot h)(5)=-10}

Explanation:


(g\cdot h)(x)=g(x)\cdot h(x)\\\\g(x)=x^2,\ h(x)=x-7\\\\\text{substitute:}\\\\(g\cdot h)(x)=(x^2)(x-7)\qquad\text{use the distributive property}\\\\(g\cdot h)(x)=(x^2)(x)+(x^2)(-7)=x^2-7x^2\\\\(g\cdot h)(5)-\text{put}\ x=5\ \text{in the expression}\\\\(g\cdot h)(5)=5^2-7(5)=25-35=-10

User Mike Dour
by
4.8k points